Use of the Glomus etunicatum as biocontrol agent of the soybean cyst nematode (Research, Society and Development, 2021)
This study investigated the effect of arbuscular mycorrhiza (Glomus etunicatum Becker & Gerd.), on the cyst nematode (Heterodera glycines Ichinohe), in a greenhouse. Mycorrhizal and non-mycorrhizal soybean plants were exposed to the pathogen at different initial population densities (0, 500, 1000, 2000, and 4000 nematodes eggs). Soybean growth, nematode reproduction, and the arbuscular mycorrhizal fungus’s capacity to decrease disease pressure were determined after 60 day-olds. The height of the plants was increased by 26% in the presence of arbuscular mycorrhizal fungus (AMF) despite of a higher initial population of cyst nematodes. The root length was, on average, 32.20% was greater in the presence of AMF. The number of nematodes females found in the root system of mycorrhizal plants was 28.21% lower than in non-mycorrhizal roots. These results suggest that AMF G. etunicatum acts indirectly, promoting an improvement in the nutritional plant status creating tolerance to the presence of the pathogen by soybean.